Apitan Tradition in Javanese and Islamic Cultural Life (A Study in Karangsari Village, Karangtengah Subdistrict, Demak Regency) - Munir, Ahmad Sirojul (Journal of Nahdlatul Ulama Studies, 2023)
Apitan (sedekah bumi) is an annual agrarian thanksgiving ritual sustained within Javanese Muslim communities and reflects the dynamics of Islam–Java acculturation, in which local practices are endowed with Islamic meanings without erasing their cultural aesthetics. Building on this context, the article formulates three focal questions: (1) what are the forms and sequences of Apitan practices in Karangsari Village, Karangtengah Subdistrict, Demak Regency; (2) what socio-cultural functions and character-education potentials does the tradition contain; and (3) how is its normative status negotiated within Islamic legal reasoning through the custom-based maxim al-‘ādah muḥakkamah. This study employs a qualitative case-study design. Data were collected in April 2022 through participant observation of the Apitan series, semi-structured interviews with local religious figures, village officials/organizers, and community members, as well as document review. The data were analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing/verification) with source triangulation and limited member checking. The findings show that Apitan in Karangsari comprises taḥtīm/khatam al-Qur’an (Qur’anic completion), a communal feast (kenduri), a harvest procession featuring gunungan (decorated piles of crops), and a wayang kulit performance as the ritual climax. Functionally, the tradition operates as ritualized gratitude for divine sustenance, a mechanism of social cohesion and inter-group religious cooperation, and an arena of informal character education transmitting religiosity, honesty, tolerance, and civic attachment. Normatively, the tradition is negotiated through al-‘ādah muḥakkamah by foregrounding gratitude–almsgiving–prayer as its core substance, while cultural forms are treated as local idioms that remain acceptable so long as they do not contradict foundational Islamic principles. Apitan is thus positioned as a cultural–religious practice that contextually mediates identity, solidarity, and Javanese Muslim piety.